Isobaric (vapour + liquid) equilibria of binary Pb-Sn and Sb-Sn system at 2Pa - Gao, Jingbao; Xu, Junjie; Yang, Bin; Kong, Lingxin; Xu, Baoqiang; You, Yanjun (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
In this paper , a new experimental method for determining vapor-liquid phase equilibrium of binary alloys was designed as show in Figure 1. The vapor liquid phase equilibrium data of Pb-Sn, Sb-Sn alloy was obtained by this scheme. The experimental data and calculated results were in good agreement with each other, which also passed the thermodynamic consistency test(Van Ness test), the y(MAD) was 0.4066 and 0.6667 respectively, which indicated that the new scheme is correct and reliable. The activity coefficient of Pb-Sn, Sb-Sn alloy were calculated by the molecular interaction volume model. The maximum average relative deviation Si and maximum average standard deviation Si* are ±1.24% and ±0.009, respectively. which proves that the calculation of the activity coefficient of the Pb-Sn and Sb-Sn alloy components by MIVM is reliable. The VLE phase diagram offer an valid and intuitive way to analyze the product compositions dependence of temperature and pressure during the process of vacuum distillation. This will be of important guiding significance to the actual production of vacuum metallurgy.